Diretrizes para a definição de ações estratégicas para tornar uma empresa da construção civil sustentável sob o aspecto econômico, social e ambiental (ESA) - Araldi, Jeancarlos (2010)
The Building Industry has developing into a dynamic market, which over the times needs to adapt in the environmental conditions. Environmental conditions are involved to use available resources to attend market demands bringing a good quality of life. The business activities are not restricted to the economic but also social and environment effects especially in the building industry. The present text was focused in a building company where is located in Passo Fundo from Rio Grande do Sul, Brazil. It was seen some descriptions and actions to apply on that company to become a sustainable industry using the ESA method. The survey was collected through of documents, questionnaire, interviews and visits in loco. The result showed through of the Method that the company management should assess the business sustainable and also being looking for tendencies in new sceneries. Therefore the company studied has showed as a intermediate. When it has been analyzing it was showed that the company could to take advantage in the scenery to making a better way of sustainable business, setting down on the competitive market